The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s41465-017-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits the Most? Individual Differences in the Transfer of Executive Control Training Across the Lifespan

Abstract: Training studies have shown that cognitive plasticity, that is the potential modifiability of a person's cognitive abilities, is considerable across the lifespan and extends to very old age. Cognitive training can not only result in significant performance improvements on the trained tasks, but also benefit performance on new untrained tasks (transfer). However, even though interventions can be very successful at the group level, individual differences in training gains tend to be large. Why do some individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 54 publications
2
62
1
Order By: Relevance
“…increases in alpha power) as compared to complex span training or a control intervention. Interestingly, and similar to Karbach et al, 2017, they found that individuals with lower working memory performance at baseline seem to benefit more from training than high-performing individuals. However, there was no indication for far transfer to matrix reasoning.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…increases in alpha power) as compared to complex span training or a control intervention. Interestingly, and similar to Karbach et al, 2017, they found that individuals with lower working memory performance at baseline seem to benefit more from training than high-performing individuals. However, there was no indication for far transfer to matrix reasoning.…”
supporting
confidence: 64%
“…Interestingly, while some papers in this Special Topic (e.g., Blacker et al, 2017; Karbach et al, 2017) find that training interventions are most beneficial for those with lower baseline abilities, other papers (e.g. Guye et al, 2017, Strobach & Huestegge, 2017) find the opposite.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Another caveat that might have contributed to the relatively small effects is that our population consisted of typically developing children from predominantly privileged backgrounds, and thus, our results might have been affected by restricted range issues. There is evidence that participants with lower baseline ability levels typically improve more in training and transfer than their high‐ability peers (e.g., Jaeggi, Karbach, & Strobach, ; Jaeggi et al., ; Karbach, Könen, & Spengler, ), and furthermore, children from low SES backgrounds seem to show especially large improvements in EF after targeted training, presumably since they are at a higher risk of having deficits in those areas, and consequentially, they have more room to improve (Blair & Raver, ; Segretin et al., ). Due to time restrictions with testing, it is important to note that we only implemented one test per cognitive domain and thus, we are not able to determine whether any improvements would hold on a latent level, that is, whether our results would extend beyond those specific tasks that we used here.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that the degree to which participants improved their understanding of themselves predicted their improvements in understanding others' mental states. Third, the articles by Blacker et al (2017) and Karbach et al (2017) highlight that the search for effective cognitive interventions will not benefit from Bone-size-fits-all^approaches, and that we need tailored interventions in order to maximize the training outcomes. As pointed out by Jaeggi et al (2017), the question in the field of cognitive training really should be Bwhat type of training is best for whom?^.…”
mentioning
confidence: 99%